Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5027/andgeov42n1-a01
|View full text |Cite
|
Sign up to set email alerts
|

Cambio hidrológico asociado al Último Maximo Glacial-Altitermal durante la transición Pleistoceno-Holoceno en el borde oriental de Puna Norte.

Abstract: ABSTRACT. The environment of the Andean Puna Plateau is mostly characterized by the dominance of evaporative processes due to aridity. Since the intermittent runoff lacks the morphodynamic competence to generate the present day landscape, authors have usually considered that the Puna landscape is a remnant feature of the Miocene arid-climate persistence. Then, a Quaternary-sensu lato-age was assigned to salars, alluvial fans and other geomorphologies. We present evidences from the endorheic depression of Guaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Diatoms could alternatively live in situ within the peat matrix, although the low pH of SV1 (generally < 4) would likely restrict diatoms to a few tolerant genera (mainly Eunotia, Nitzschia and Pinnularia ; Denicola, 2000). The diverse diatom assemblage found in the core ash is more likely to flourish in the more neutral/basic conditions common to the endorheic basins of the Puna (López Steinmetz and Galli, 2015; McGlue et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms could alternatively live in situ within the peat matrix, although the low pH of SV1 (generally < 4) would likely restrict diatoms to a few tolerant genera (mainly Eunotia, Nitzschia and Pinnularia ; Denicola, 2000). The diverse diatom assemblage found in the core ash is more likely to flourish in the more neutral/basic conditions common to the endorheic basins of the Puna (López Steinmetz and Galli, 2015; McGlue et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the scarce representation or even complete absence of the Late Glacial and Holocene sedimentary record could be explained by local geomorphological inactivity or by recent eolian deflation. Similarly at Laguna de Pozuelos (McGlue et al, 2013) and Laguna Guayatayoc (López Steinmetz and Galli, 2015), there is also a noticeable reduction of the record during the last 20,000 cal. years BP while Sierra de Santa Victoria and Zenta have better records for the Pleistocene-Holocene transition (Schäbitz et al, 2001;Zech et al, 2009).…”
Section: Paleoenvironmental Interpretationmentioning
confidence: 99%
“…Several authors suggest the development of paleolakes in Sierra de Santa Victoria and Laguna Guayatayoc as a consequence of glacier melting and precipitation increase between 20,000 and 17,000 cal. years BP (Zech et al, 2009;López Steinmetz and Galli, 2015) and in Laguna de los Pozuelos, McGlue et al (2013) identified a lithostratigraphic unit which characterize a predominantly palustrine environment between 37,000 and 23,000 cal. years BP.…”
Section: Introductionmentioning
confidence: 99%